Mutations targeting the coagulation pathway are enriched in brain metastases - Cristina Richichi (Nature Portfolio, 2017)
Abstract Brain metastases (BMs) are the most common malignancy of the central nervous system. Recently it has been demonstrated that plasminogen activator inhibitor serpins promote brain metastatic colonization, suggesting that mutations in serpins or other members of the coagulation cascade can provide critical advantages during BM formation. We performed whole-exome sequencing on matched samples of breast cancer and BMs and found mutations in the coagulation pathway genes in 5 out of 10 BM samples. We then investigated the mutational status of 33 genes belonging to the coagulation cascade in a panel of 29 BMs and we identified 56 Single Nucleotide Variants (SNVs). The frequency of gene mutations of the pathway was significantly higher in BMs than in primary tumours, and SERPINI1 was the most frequently mutated gene in BMs. These findings provide direction in the development of new strategies for the treatment of BMs.